2014
DOI: 10.2355/isijinternational.54.582
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors and Effects of Assimilation Characteristic of Iron Ores in Sintering Process

Abstract: Iron ore's assimilation characteristic reflecting the beginning formation temperature of liquid phase in sintering process plays very important role on the fluidity of liquid phase and bonding strength of sinter body. Experimental study of assimilation characteristics of 12 kinds of iron ores were conducted using micro-sinter equipment, and pure reagent simulating tests of assimilation characteristic were also carried out for the purpose of achieving the influence of chemical composition on the assimilation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 14 publications
3
21
3
Order By: Relevance
“…For the 5 kinds of V-Ti iron ores, with increase of SiO 2 , ATs decreased in a total view. And this is consistent with the previous results (Yang and Davis, 1999;Wu et al, 2014). According to the results (Wu et al, 2014), SiO 2 contributed to reduce the AT of Fe 2 O 3 , in addition, according to the thermodynamic, with the SiO 2 content increasing, eutectic mixtures 2FeO·SiO 2 -2CaO·SiO 2 with melting point of 1150°C, and 2FeO·SiO 2 -Fe 2 O 3 with melting point of 1142°C were also could be formed, all of which lowed the AT.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For the 5 kinds of V-Ti iron ores, with increase of SiO 2 , ATs decreased in a total view. And this is consistent with the previous results (Yang and Davis, 1999;Wu et al, 2014). According to the results (Wu et al, 2014), SiO 2 contributed to reduce the AT of Fe 2 O 3 , in addition, according to the thermodynamic, with the SiO 2 content increasing, eutectic mixtures 2FeO·SiO 2 -2CaO·SiO 2 with melting point of 1150°C, and 2FeO·SiO 2 -Fe 2 O 3 with melting point of 1142°C were also could be formed, all of which lowed the AT.…”
Section: Resultssupporting
confidence: 92%
“…However, it was needed to be pointed out that the ATs of V-Ti magnetite iron ores were lower than ATs of hematite (YD, NF) in total, and this is in contrast with the previous results (Yang and Davis, 1999;Wu et al, 2014). The research of Wu et al (2014) indicated that the ATs of magnetite were higher than that of hematite.…”
Section: Resultscontrasting
confidence: 71%
“…Wu et al [9] reported on the basic characteristics of ore, including the assimilation characteristics, the fluidity of liquid phase, and the self-strength of bonding phase. In addition, the assimilation and fluidity of liquid phase have been thoroughly studied [10][11], such as the blending optimization based on the assimilation and fluidity of liquid phase [12].…”
Section: Introductionmentioning
confidence: 99%
“…15 and T 10% of the sinter might be caused by the generation of the high-melting-point 2CaO·SiO 2 . The 2CaO·SiO 2 in the sinter can undergo a crystal transition during cooling, leading to the formation of small cracks in the sinter.…”
Section: Sinter Mineral Composition and Morphologymentioning
confidence: 99%
“…With the rapid development of high-grade burden and large-scale BFs, sinter plays an increasingly important role in determining the operating conditions of BFs. However, the current status of the iron and steel market is weak; high production costs have become the main obstacle for the survival and development of steel enterprises [1][2][3]. Therefore, reducing production costs has become the primary task for the sustainable development of metallurgical processes.…”
Section: Introductionmentioning
confidence: 99%